True triaxial strength and failure characteristics of cubic coal and sandstone under different loading paths. (November 2020) - Lu, Jun; Yin, Guangzhi; Zhang, Dongming; Gao, Heng; Li, Cunbao; Li, Minghui
Abstract: In deep underground coal mining, engineering activities are performed within anisotropic in-situ stress fields due to engineering disturbances and tectonic stress. Many such activities involve the development of excavations in soft rock and anisotropic coal. Accordingly, studying the mechanical properties of soft rocks is important for the stability of deep underground excavations. In this study, the deformation, strength, and failure characteristics of soft sandstone and raw coal under two different true triaxial loading paths were investigated using a self-developed true triaxial test apparatus. The results indicated that the inelastic strain in the pre-peak stage of sandstone and coal gradually increased with increasing intermediate principal stress. Also, the strength-drop in the post-peak stage increased. The crack initiation stress, crack damage stress, and peak strength of sandstone and coal first increased and then decreased with increasing intermediate principal stress for a given σ3 . Moreover, with increasing intermediate principal stress, the failure mode of sandstone and coal changed from shear to tensile shear, and from brittle to semi-brittle. The linear Mogi criteria as found to characterize the true triaxial strength of coal well, while the modified Lade criteria was more applicable to soft sandstone. Owning to the symmetry assumption, the linear Mogi criteria predicted low strength when the intermediate principal stress coefficient exceeded to 0.5. In addition, the peak strength curve of rock on the π plane and the influence of weak structures on the failure mode of anisotropic coal was discussed. Weak structures have an important influence on the failure mode of coal, which depends on the strength difference between the structural plane and the coal rock mass. The strength envelope on the π plane had a significant stress Lode angle effect, which gradually decreased as the mean stress increased. Highlights: Influence of the intermediate principal stress on deformation, strength, and failure mode of sandstone and coal. Different Mogi-type strength criteria were discussed and compared. The interval effect of intermediate principal stress on coal rock strength was discussed. The envelope of true triaxial strength of rocks on the π plane was discussed. The influence of weak structures on the failure mode of coal was discussed.